2015
DOI: 10.1371/journal.pone.0135489
|View full text |Cite
|
Sign up to set email alerts
|

Parity and Longevity of Aedes aegypti According to Temperatures in Controlled Conditions and Consequences on Dengue Transmission Risks

Abstract: BackgroundIn Guadeloupe, Aedes aegypti mosquitoes are the only vectors of dengue and chikungunya viruses. For both diseases, vector control is the only tool for preventing epidemics since no vaccine or specific treatment is available. However, to efficiently implement control of mosquitoes vectors, a reliable estimation of the transmission risks is necessary. To become infective an Ae. aegypti female must ingest the virus during a blood meal and will not be able to transmit the virus during another blood-meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 38 publications
3
65
0
1
Order By: Relevance
“…Other studies have shown that warmer temperature enhances dengue virus multiplication through shortening the extrinsic incubation period [59][60][61] and shortens the extrinsic incubation period of DENV within mosquitoes [60,62]. The best temperature range for survival of Aedes mosquitoes is between 18 and 27°C [10,[63][64][65][66][67]. During the dry season with no piped water, people are forced to store water in containers especially in areas with water shortage, which in turn provides a breeding site form Aedes mosquitoes [68,69].…”
Section: Variablesmentioning
confidence: 99%
“…Other studies have shown that warmer temperature enhances dengue virus multiplication through shortening the extrinsic incubation period [59][60][61] and shortens the extrinsic incubation period of DENV within mosquitoes [60,62]. The best temperature range for survival of Aedes mosquitoes is between 18 and 27°C [10,[63][64][65][66][67]. During the dry season with no piped water, people are forced to store water in containers especially in areas with water shortage, which in turn provides a breeding site form Aedes mosquitoes [68,69].…”
Section: Variablesmentioning
confidence: 99%
“…Low environmental temperatures will prolong the mosquito reproduction cycle thus decreasing the frequency of blood sucking. Low environmental temperatures will also prolong the EIP of dengue virus (Goindin et al, 2015) (Table 2) is likely to be that rainfall can have a negative or positive impact on the capacity of mosquito's vectors. More in-depth research is needed to discover the effects of precipitation on dengue cases more precisely.…”
Section: Climate-dengue Incidencementioning
confidence: 99%
“…In this case, it was the difference between declaring a risk for outbreak or not ( Figure 5). Many things affect vector competence including vector species, discrete populations within species, and environmental factors [1, 14,19,20,28,40,42,43]. Several recent studies have focused on environmental factors such as temperature, and found that temperature not only affects vector competence of many arboviruses, especially in Aedes aegypti, but also several life traits of the mosquito [27,39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Cartons were checked daily and, when present, dead mosquitoes were counted and removed up to 28 dpe (approximately 1 month), as this has been shown to be the upper limit of believed survival of Ae. aegypti and is similar to the range used in Tesla, et al [27,28]. Only mosquitoes that took all offered bloodmeals were included in the mortality analyses.…”
Section: Mortality Studymentioning
confidence: 99%
See 1 more Smart Citation